2008
DOI: 10.1016/j.otohns.2008.05.010
|View full text |Cite|
|
Sign up to set email alerts
|

Balloon catheter sinusotomy: One‐year follow‐up—Outcomes and role in functional endoscopic sinus surgery

Abstract: Balloon catheter sinusotomy results were durable over the study period, showing long-term effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
99
0
6

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(114 citation statements)
references
References 15 publications
9
99
0
6
Order By: Relevance
“…A prospective multicenter CLEAR (Clinical evaluation to confirm safety and efficacy of sinuplasty in the paranasal sinuses) study of 115 patients across 9 physician practices, highlighted an impressive safety profile (zero adverse events), durability of patency (98% patency of observed ostia after 6 months), and significant improvement in patient symptoms and quality of life [12]. Of the 20 patients in our study assessed by diagnostic nasal endoscopy at periodic intervals, 92% had widely patent ostia from their first review at 1 week postoperatively till the completion of 1 year of follow up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A prospective multicenter CLEAR (Clinical evaluation to confirm safety and efficacy of sinuplasty in the paranasal sinuses) study of 115 patients across 9 physician practices, highlighted an impressive safety profile (zero adverse events), durability of patency (98% patency of observed ostia after 6 months), and significant improvement in patient symptoms and quality of life [12]. Of the 20 patients in our study assessed by diagnostic nasal endoscopy at periodic intervals, 92% had widely patent ostia from their first review at 1 week postoperatively till the completion of 1 year of follow up.…”
Section: Discussionmentioning
confidence: 99%
“…Careful case evaluation & selection remains paramount in providing the best outcomes with this technique. Balloon Sinuplasty has tangible benefits such as a reduction in invasiveness of the intervention, hospital stay, recovery time, post-operative debridements, post-operative medications, and office follow-up visits [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…In our 2-year follow-up study we demonstrated that patient satisfaction and symptom reduction were equal in both groups. However, in number of acute exacerbations ESS seems to be superior to balloon sinuplasty [14].…”
Section: Introductionmentioning
confidence: 91%
“…In September 2005, Balloon Sinuplasty TM (Acclarent, Inc.) was introduced as a minimally invasive option to widen sinus ostia and their transition spaces while preserving the corresponding mucosa. The outcome, efficacy, and safety of the balloon dilation technology as applied to the frontal, maxillary and sphenoid sinuses has been well vetted and reported [2][3][4][5][6][7][8][9]. However, due to the complex drainage patterns and interconnected nature of the ethmoid complex, the balloon technology was not initially suited to treat chronic ethmoid disease [10].…”
Section: Introductionmentioning
confidence: 99%